Pemberitaan TV Lokal dan Pembangunan Daerah Berkelenjutan di Indonesia: Studi Intensif Pada Konten Berita Pembangunan Daerah Berkelanjutan di TVRI Sulawesi Tenggara - Larisu, Zulfiah; Prajarto, Nunung; Subejo, Subejo (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This study aims to find the profile of sustainable regional development news on local television Southeast Sulawesi Province. The method used in this research is the analysis of the content (content analysis) with the overall population is news item broadcast by local television stations in Southeast Sulawesi Province in the period of October 1, 2015 to March 31, 2016, and the samples are news items which are included in regional development sustainable regional development issues. Determining sample news item carried by purposive sampling, and data were collected by using coding sheet and the results were analyzed using descriptive statistics. This research resulted in 584 news items about sustainable regional development in hardnews news format, the type of news one side, the source of the news of the government at the provincial level. Media content covers issues or problems of development progress in the economic, social, environmental, socio-economic, the social environment, environmental economics, as well as socio-economic and environmental fields. Actors involved in the development of individuals who are on official institutions and government offices. This suggests that sustainable regional development in Southeast Sulawesi Province has done and getting positive attention for local television.